Regional cuisine as a catering concept that increases the tourist flow to the Russian regions - T. A. Dzhum; S. K. Kuizheva; M. Yu. Tamova (Новые технологии, 2022)
The article presents an overview of business concepts in the field of restaurant business, allowing to maintain consumer interest in the products and services offered using the capabilities of the Krasnodar Territory. The purpose of the research is to identify the main driving forces of the development of restaurant projects, focusing on the relevance of consumer properties of catering products for consumers, applying a differentiated approach to them and focusing on what can lead to success. The research methods used are analysis, synthesis, generalization, observation and forecasting. The results and discussion: the article highlights the role of tourism in the development of catering enterprises as an engine of business concepts aimed at the tourist audience and related to the promotion of regional cuisine. For the next few years, the concept of a local cuisine has a huge prospect. In all regions of Russia this particular direction will be developing in the near future – local cuisine, the Russian cuisine, old recipes, unusual farm products. The state support of tourism will also increase interest in HoReCa. Conclusions: The Krasnodar Territory is a developing tourist, multinational, creative region open to innovations. Restaurateurs, culinary specialists and confectioners monitor the state of the hospitality industry in Russia and in the world, constantly seeking professional recognition, gaining more and more recognition, the Ministry of Resorts, Tourism and Olympic Heritage and the Department of Consumer Sphere and Regulation of the Alcohol Market of the Krasnodar Territory stimulate the promotion of the restaurant image of the Kuban in various levels, holding professional forums, festivals, exhibitions for HoReCa industry specialists, opens up new opportunities for the exchange of experience, facilitating the acquisition of new knowledge, communication with suppliers, and acquaintance with gastronomic trends.